Laparoscopic and open surgery with D3-lymphadenectomy in patients with left-sided colon cancer: clinical and pathological parallels - P. V. Tsarkov; I. V. Reshetov; I. A. Tulina; A. Yu. Kravchenko; D. N. Fedorov; A. V. Leontyev (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To evaluate morphological characteristics of the resected specimen after open and laparoscopic surgery with D3-lymphadenectomy for left-sided colon cancer. Material and methods. The investigation was designed as retrospective-prospective comparative case-match study. From archival cases and prospectively collected database cases with left-sided colon cancer stage I-III treated by complete mesocolic excision (CME) with D3-lymphadenectomy were selected. Patients who underwent open surgery formed the first group. The second group included patients after laparoscopic surgery. Results. Each group consisted of 54 patients. There were no significant differences in terms of age, gender, body mass index, tumor location, and tumor stage between the two groups. No statistically significant difference in specimen morphological characteristics after open and laparoscopic surgery with D3-lymphadenectomy for left-sided colon cancer was observed. Conclusion. The feasibility and safety of laparoscopic technique in treatment of left-sided colon cancer is reasonable regarding to the specimen quality. Similar clinical and pathological results suggest that there is no oncological difference between open and laparoscopic techniques with D3-lymphadenectomy for left-sided colon cancer. However, further studies are required to estimate long-term oncological results.